1999
DOI: 10.1029/1998rs900026
|View full text |Cite
|
Sign up to set email alerts
|

A statistical framework for space‐based EUV ionospheric tomography

Abstract: Abstract. We present a statistical reconstruction framework for space-based extreme ultraviolet (EUV) ionospheric tomography. The EUV technique offers a means to invert the nighttime F region electron density on global scales from a single spaceborne spectrograph, using prominent optically thin emissions produced by radiative recombination of O +. Since the EUV technique does not rely on ground receivers to make the measurements, the observations do not suffer from limitations on the viewing angles. The EUV to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
(6 reference statements)
0
38
0
Order By: Relevance
“…The descending node of each TIMED orbit provides two views of the plasma depletions having a component normal to the magnetic field from which tomographic retrievals of electron densities may be performed (Kamalabadi et al, 1999(Kamalabadi et al, , 2002Comberiate et al, 2007). The major assumption was that electron density fluctuations were approximately constant along magnetic field lines.…”
Section: Implications Of Plasma Measurements For Gw Parametersmentioning
confidence: 99%
“…The descending node of each TIMED orbit provides two views of the plasma depletions having a component normal to the magnetic field from which tomographic retrievals of electron densities may be performed (Kamalabadi et al, 1999(Kamalabadi et al, , 2002Comberiate et al, 2007). The major assumption was that electron density fluctuations were approximately constant along magnetic field lines.…”
Section: Implications Of Plasma Measurements For Gw Parametersmentioning
confidence: 99%
“…They can explicitly handle any observing geometry and can account for instrument sensitivity variations, hot spots, etc. They can also produce an estimate of the probable error at all points in the resulting image and can adjust the image resolution to give the best results for a given data set S/N (Kamalabadi et al 1999). Unfortunately, they scale quite badly with image size.…”
Section: Singular Value Decompositionmentioning
confidence: 99%
“…Dymond and Thomas [1999, 2001] and Kamalabadi et al [1999] recently demonstrated tomographic inversion algorithms for determining the two‐dimensional, altitude versus latitude, distribution of the F region electron density. These algorithms simultaneously invert a set of limb observations of the recombination radiation to produce the electron density.…”
Section: Introductionmentioning
confidence: 99%